Immunological memory in latent Japanese encephalitis virus infection. - Kulshreshtha, R. (1988)
Long term B-cell memory to Japanese encephalitis virus (JEV) in latently infected mice was investigated by adoptive cell transfer. Both IgM and IgG memory were elicited by antigen challenge or cyclophosphamide induced reactivation of virus. A weak antigen-specific IgM response for a brief period and a strong IgG response were detected in Swiss albino mice exposed to secondary infection. A correlation between the secondary IgM antibody and protection against JEV challenge was observed in adoptive transfer experiments. This was abrogated by pretreatment of the serum with 2-mercaptoethanol. Similarly secondary immune splenic T-cells up to day 5 post-reactivation provided protection. These results suggest that a long term antigen-specific IgM and IgG memory was induced by JEV challenge in latently infected mice. Further, the role of IgM antibody and T-cells in the response of mice to secondary JEV infection has been shown.